2018
DOI: 10.1016/j.jaad.2017.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis: A diagnostic dilemma

Abstract: References1 Concha JSS, Pena S, Gaffney RG et al.; Skin Myositis Delphi Group. Developing classification criteria for skin-predominant dermatomyositis: the Delphi process. Br J Dermatol 2020; 182: 410-7. 2 Concha JSS, Tarazi M, Kushner CJ et al. The diagnosis and classification of amyopathic dermatomyositis: a historical review and assessment of existing criteria. Br J Dermatol 2019; 180:1001-8. 3 Lundberg IE, Tj€ arnlund A, Bottai M et al.; International Myositis Classification Criteria Project Consortium, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…There have been several multidisciplinary attempts to come up with diagnostic and classification criteria to characterize better this skin‐predominant form of DM, especially as the risk of internal malignancy and interstitial lung disease is present among patients with purely cutaneous findings . Despite these efforts, a significant number of patients with ADM have been misclassified as having lupus erythematosus, undifferentiated connective tissue disease (UCTD) or mixed connective tissue disease (MCTD) when they present with skin findings in the background of autoimmune or rheumatological complaints . The dangers of erroneous classification include the inability to screen for comorbidities, inadequate treatment and the exclusion of patients from clinical research and experimental trials …”
Section: Bohan and Peter's Diagnostic Criteria For Dermatomyositis (Dm)mentioning
confidence: 99%
“…There have been several multidisciplinary attempts to come up with diagnostic and classification criteria to characterize better this skin‐predominant form of DM, especially as the risk of internal malignancy and interstitial lung disease is present among patients with purely cutaneous findings . Despite these efforts, a significant number of patients with ADM have been misclassified as having lupus erythematosus, undifferentiated connective tissue disease (UCTD) or mixed connective tissue disease (MCTD) when they present with skin findings in the background of autoimmune or rheumatological complaints . The dangers of erroneous classification include the inability to screen for comorbidities, inadequate treatment and the exclusion of patients from clinical research and experimental trials …”
Section: Bohan and Peter's Diagnostic Criteria For Dermatomyositis (Dm)mentioning
confidence: 99%
“…In addition, there can be interdisciplinary challenges among rheumatologists, neurologists and dermatologists in classifying these patients given the nuances of skin findings in DM . It is not surprising that a retrospective study showed that 55·6% of patients had an alternate diagnosis prior to ultimately being diagnosed as having DM, with a median time delay from presentation to diagnosis of about 15 months . Altogether, 37·2% of those alternate diagnoses were either systemic lupus erythematosus or cutaneous lupus erythematosus (CLE) .…”
mentioning
confidence: 99%
“…Dermatomyositis (DM) is a heterogeneous autoimmune inflammatory disease that can be challenging to classify, particularly in patients who present predominantly with cutaneous disease. 1 Unfortunately, skin-predominant DM has historically been left out of several classification criteria schemata, [2][3][4] which has resulted in improper classification of patients and a delay in appropriate treatment and screenings. 5 In addition, there can be interdisciplinary challenges among rheumatologists, neurologists and dermatologists in classifying these patients given the nuances of skin findings in DM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Dr Victoria Werth, has shown that up to 26% of patients with ADM still fail to meet the diagnostic criteria set forth in the 2017 EULAR/ACR IIM classification . Additional work has also shown a significant percentage of patients with skin‐predominant ADM are misdiagnosed as having cutaneous lupus erythematosus . Failure to appropriately diagnose these patients as having DM is concerning for several reasons.…”
mentioning
confidence: 99%